Aliran al-Qadariyyah: perkembangan, pengaruh dan kesannya di alam Melayu dan khususnya di Malaysia - Wan Ali, Wan Zailan Kamaruddin (Akademi Pengajian Melayu, Universiti Malaya, 2002)
Al-Qadariyyah is considered one of the earliest sects in the history of Islamic Thought. In the Umayyad period, they emerged but then harshly condemned and cursed by the muslims and slowly disappeared. This article as the title shown is an attempt to explain the emergence and developments of al-Qadarites and also to analyse the influences and impacts of their thoughts in the muslim world in general and Malaysia in particular.